2013
DOI: 10.1177/1541931213571307
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mindfulness and Resiliency among Active Duty Service Members and Military Veterans

Abstract: Soldier resilience is of paramount importance to the U.S. Military. Mindfulness and Resilience are positively correlated to one another in research focused on civilian populations. Since mindfulness can be learned, if the correlations remain consistent over time, then perhaps resilience can be increased by learning to be mindful. However, no published research has investigated the relationship between mindfulness and resilience among military active duty and veteran populations who have not undergone mindfulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Randomized controlled trials have found that mindfulness-based interventions (MBIs) improve mental health (e.g., PTSD and depressive symptoms, anxiety, chronic stress) and physical functioning (e.g., functional status, chronic pain), and assist in the treatment of insomnia and substance use disorders (Chiesa & Serretti, 2011; Khusid & Vythilingam, 2016a; Khusid & Vythilingam, 2016b). Among individuals exposed to high-stress work environments, such as first-responders (Christopher et al, 2016) and soldiers in intensive field training (Rice, Boykin, Overby, Jeter, & Villarreal, 2017), MBIs have been shown to improve emotion regulation, sleep quality, physical health, and work performance.…”
Section: Developing a Rationale For Expending Resources On Mindfulnessmentioning
confidence: 99%
“…Randomized controlled trials have found that mindfulness-based interventions (MBIs) improve mental health (e.g., PTSD and depressive symptoms, anxiety, chronic stress) and physical functioning (e.g., functional status, chronic pain), and assist in the treatment of insomnia and substance use disorders (Chiesa & Serretti, 2011; Khusid & Vythilingam, 2016a; Khusid & Vythilingam, 2016b). Among individuals exposed to high-stress work environments, such as first-responders (Christopher et al, 2016) and soldiers in intensive field training (Rice, Boykin, Overby, Jeter, & Villarreal, 2017), MBIs have been shown to improve emotion regulation, sleep quality, physical health, and work performance.…”
Section: Developing a Rationale For Expending Resources On Mindfulnessmentioning
confidence: 99%
“…See Rice et al (2013) for contrary findings involving the MAAS in a sample of military service members.…”
mentioning
confidence: 99%
“…In another study, Keye and Pidgeon (2013) found that both mindfulness and academic self-efficacy significantly predict resilience in university students. Conversely, Rice et al (2013) indicated no direct significant relationship between overall mindfulness and resilience in active duty service members and military veterans. In addition, similar to the theoretical standing of the current study, there are also studies showing that the relation between mindfulness and trait resilience is only mediated by certain psychological constructs such as emotion regulation and self-compassion in socio-economically disadvantaged adolescents (Sünbül-Aydın & Güneri, 2019) and me-diated by self-esteem in university students (Bajaj, 2017).…”
Section: Mindfulness and Trait Resiliencementioning
confidence: 84%